Frequency of alcohol consumption by patients hospitalized in a general hospital in Iran - Abdollah Farhadi Nasab, Mostafa Hamdieh, Jahanfar Vahidi, Seyed-Mostafa Hosseini-Zijoud (Journal of Applied Pharmaceutical Science, 2017)
This study aim to assess the frequency of alcohol consumption in 536 patients hospitalized in a general hospital during 2014. The Alcohol Use Disorders Identification Test (AUDIT-C) questionnaire was used to identify alcohol consumption. The cut-off point for heavy alcohol consumption was 4 in males and 3 in females. P less than 0.05 was considered statistically significant. The mean age of patients was 46.93 years; 43.8% were males and 56.2% were females; 20% were single, 67.5% were married and 12.5% were divorced or widowed. The frequency of alcohol consumption in the previous year was 12.9% among patients. The highest frequency was noted in patients hospitalized in the Psychiatric Ward (25.6%) and the lowest frequency was reported by patients hospitalized in the Gynecology Ward (3.2%). Alcohol consumption has a considerably high frequency among hospitalized patients. Considering its effect on the morbidity and mortality, knowledge in this regard can help in better management of conditions, enhance the efficacy of treatment of patients and decrease the related costs by shortening the hospitalization period. Further studies are required to cast a definite judgment in this respect.
Keywords: Addiction, Alcohol consumption, AUDIT-C, General Hospital.